Temperature-Responsive Molecular Assemblies Using Oligo(Ethylene Glycol)-Attached Polyamidoamine Dendron Lipids and their Functions as Drug Carriers - Takuya Hashimoto; Yuji Hirai; Eiji Yuba; Atsushi Harada; Kenji Kono (Journal of Functional Biomaterials, 2020)
Temperature-responsive nanocarrier systems using external stimuli are one of the most widely investigated stimuli-responsive strategies because heat is easy and safe to use for hyperthermia and controlled drug delivery. Polyamidoamine dendron lipids (PAMAM-DLs) composed of PAMAM dendron as head group and two alkyl chains can exhibit temperature-responsive morphological change through the attachment of suitable moieties to terminal of PAMAM dendron. In this study, oligo(ethylene glycol)s including ethoxy- or methoxy-diethylene glycols were attached to the terminals of PAMAM-DL, and temperature-responsive properties of their self-assemblies were evaluated by calorimetric and turbidity measurements. In the evaluation of temperature-responsive properties, ethoxy diethylene glycol (EDEG)-attached PAMAM-DL composed of two saturated alkyl chains and PAMAM dendron with 1st generation had lipid bilayer structure and suitable cloud point for the application as drug carrier. In vitro performances of the assemblies combining EDEG-attached PAMAM-DLs with cholesteryl-oxy-poly(ethylene glycol) (PEG-Chol) was evaluated using doxorubicin (DOX) as an anticancer drug. Cellular uptake of DOX-loaded EDEG-attached PAMAM-DL/PEG-Chol assemblies was promoted at 42 °C rather than 37 °C, resulting in an effective decrease in cell viability.